Germination Under Temperature Stress Facilitates Invasion in Indehiscent Lepidium Species - Said Mohammed; Klaus Mummenhoff (Agriculture)
This study investigates the germination ecology of three Lepidium species, including the invasive, indehiscent-fruited Lepidium appelianum and Lepidium draba, and the invasive, dehiscent-fruited Lepidium campestre. The ability of Lepidium species to germinate under a wide range of temperature conditions is significant for understanding their potential invasiveness and establishment in novel and extreme environments. This study aims to clarify the germination behavior of L. appelianum, L. draba, and L. campestre, thereby enhancing our understanding of their invasive potential and ecological implications in the context of a changing climate. The base (Tb), optimum (To), and maximum temperatures for 50% germination (Tc(50)) were determined across a broad thermal gradient following standard protocols. Freshly harvested seeds and fruits of L. appelianum are non-dormant. In contrast, L. draba exhibit pericarp-mediated chemical dormancy, while L. campestre demonstrates physiological dormancy, which is released through after-ripening. The results indicate that L. appelianum and L. draba seeds and fruits germinate at a base temperature (Tb) of 1 °C and 4 °C, respectively. On the other hand, L. campestre seeds germinate at a Tb of 5.8 °C. The optimum temperature (To) for the germination of seeds and fruits in L. appelianum and L. draba ranges from 23 °C to 25 °C, while the To for L. campestre seed germination is 16 °C to 18 °C. Additionally, the maximum temperature for 50% germination (Tc(50)) for L. appelianum fruits is 39.8 °C, for L. draba it is 34.4 °C, and L. campestre reports a (Tc(50)) ranging from 27.4 °C to 33.3 °C for freshly harvested and after-ripened seeds, respectively. These results demonstrated that L. appelianum and L. draba can germinate across a broad temperature range, from very cold to very hot, unlike L. campestre. These findings suggest that the unique reproductive strategy of indehiscent fruits, coupled with a wide thermal germination niche, may contribute to the invasive success of L. appelianum and L. draba. Given the projected climate warming, the results highlight the potential for increased invasiveness of these species and suggest the need for targeted management strategies.